(untitled) (IUPHAR/BPS Guide to Pharmacology CITE, 2019)
Melatonin receptors (nomenclature as agreed by the NC-IUPHAR Subcommittee on Melatonin Receptors [36]) are activated by the endogenous ligands melatonin and clinically used drugs like ramelteon, agomelatine and tasimelteon.